2022
DOI: 10.1186/s12889-022-14160-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations of childhood trauma with long-term diseases and alcohol and nicotine use disorders in Czech and Slovak representative samples

Abstract: Objective The abuse and neglect of a child is a major public health problem with serious psychosocial, health and economic consequences. The aim of this study was to assess the relationship between various types of childhood trauma, selected long-term diseases and alcohol and nicotine use disorder in Czech and Slovak representative samples. Methods Data on retrospective reporting about selected long-term diseases, alcohol and nicotine use disorder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…While we identified only four studies 115 – 118 reporting on the association with asthma, the studies reporting on this outcome consistently demonstrated a harmful effect and our model results found weak evidence of an association (0.04 ROS). Our conservative interpretation of the evidence suggests at least 9% increase in asthma risk given exposure to childhood sexual abuse, with a BPRF of 1.09.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…While we identified only four studies 115 – 118 reporting on the association with asthma, the studies reporting on this outcome consistently demonstrated a harmful effect and our model results found weak evidence of an association (0.04 ROS). Our conservative interpretation of the evidence suggests at least 9% increase in asthma risk given exposure to childhood sexual abuse, with a BPRF of 1.09.…”
Section: Resultsmentioning
confidence: 55%
“…We found weak evidence of association (one-star rating) for eight additional health outcomes: type 2 diabetes mellitus (number of accepted studies ( n ) = 7 (refs. 118 124 ); −0.01 ROS), HIV/AIDS ( n = 7 (refs. 44 , 47 , 90 , 125 128 ); −0.04 ROS), sexually transmitted infections, excluding HIV ( n = 4 (refs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher childhood trauma was associated with more severity of mental disorders. [47][48][49] Emotional and physical neglect was related to depression, anxiety, and stress. 50 1.…”
Section: Discussionmentioning
confidence: 99%